The gene expression of CALD1, CDH2, and POSTN in fibroblast are related to idiopathic pulmonary fibrosis - Wu, Shufei; Liu, Mengying; Zhang, Mingrui; Ye, Xu; Gu, Huimin; Jiang, Cheng; Zhu, Huihui; Ye, Xiaoling; Li, Qi; Huang, Xinmei; Cao, Mengshu (Frontiers in Immunology, 2024)
Idiopathic pulmonary fibrosis is a progressive lung disorder characterized by excessive collagen production and tissue scarring. However, the molecular mechanisms underlying pulmonary fibrosis are still unclear. In our study, we analyzed the expression of differential genes using TGF-β1-induced primary lung fibroblasts and lung tissues from datasets. RNA sequencing identified 475 differentially expressed genes (DEGs) in the fibrosis model. Gene expression analysis of IPF lung tissue datasets identified 94 DEGs. Functional enrichment analysis showed significant enrichment of DEGs in various biological processes, cellular components, molecular functions, and KEGG pathways. These DEGs were associated with cellular response to TGF-β, connective tissue development, extracellular matrix components, and signaling pathways such as the AGE-RAGE signaling pathway and ECM-receptor interaction. Protein-protein interaction (PPI) network analysis identified hub genes including FN1, COL1A1, POSTN, KIF11, and ECT2. Additionally, CALD1 (Caldesmon 1), CDH2 (Cadherin 2), and POSTN (Periostin) were identified as dysregulated hub genes in both the RNA sequencing and GEO datasets. Validation experiments confirmed the upregulation of CALD1, CDH2, and POSTN in TGF-β1-treated fibroblasts and IPF lung tissue samples. Additionally, Immunohistochemistry (IHC) experiments were meticulously conducted to probe the tissue-level expression patterns of these three molecules. Knockdown of CALD1, CDH2, and POSTN attenuated the expression of fibrotic markers (collagen I and α-SMA) in response to TGF-β1 stimulation in primary fibroblasts. Co-expression analysis revealed interactions between hub genes and predicted genes involved in actin cytoskeleton regulation and cell-cell junction organization. Collectively, these findings shed light on the potential roles of CALD1, CDH2, and POSTN in pulmonary fibrosis and suggest their potential as therapeutic targets for intervention.